Sequential activation of human oculomotor centers during planning of visually-guided eye movements: a combined fMRI-MEG study. - Sestieri, Carlo; Pizzella, Vittorio; Cianflone, Francesco; Romani, Gian L.; Corbetta, Maurizio (Frontiers in Human Neuroscience, 2008)
We used magneto-encephalography (MEG) to measure visually evoked activity in healthy volunteers performing saccadic eye movements to visual targets. The neuromagnetic activity was analyzed from regions of cortical activation identifi ed in separate functional magnetic resonance imaging (fMRI) studies. The latency of visual responses signifi cantly increased from the Middle Temporal region (MT+) to the Intraparietal Sulcus (IPS) to the Frontal Eye Field (FEF), and their amplitude was greater in the hemisphere contralateral to the visual target. Trial-to-trial variability of oculomotor reaction times correlated with visual response latency across cortical areas. These results support a feedforward recruitment of oculomotor cortical centers by visual information, and a model in which behavioral variability depends on variability at different neural stages of processing.